2000
DOI: 10.1038/oby.2000.9
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Subpopulation Distributions in Lean, Obese, and Type 2 Diabetic Women: A Comparison of African and White Americans

Abstract: Results: AA diabetic women, like WA diabetic women, had a larger average very low density lipoprotein (VLDL) size, elevated levels of small low density lipoprotein cholesterol (LDL-C), and lower levels of small high density lipoprotein cholesterol (HDL-C), when compared to lean controls (p Ͻ 0.05). These differences were accompanied by higher VLDL-triglycerides (TG) and LDL-C in WA (p Ͻ 0.05), but not in AA. Although the effects of obesity and diabetes on lipoprotein subpopulation were fairly similar for AA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…It has been suggested that the potential antiatherogenic effects of the e2 allele involving lower LDL cholesterol levels may be offset by the accumulation of atherogenic large VLDL cholesterol and remnant triglyceride-rich lipoproteins (4,8,39). In agreement with previous population studies (25,40,41), Caucasians had substantially higher levels of plasma triglyceride compared with African Americans. Therefore, we hypothesize that the relatively lower triglyceride levels in African Americans may enhance a favorable effect of the apoE genotype, whereas a protective effect of e2 in Caucasians might be offset by higher triglyceride levels.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that the potential antiatherogenic effects of the e2 allele involving lower LDL cholesterol levels may be offset by the accumulation of atherogenic large VLDL cholesterol and remnant triglyceride-rich lipoproteins (4,8,39). In agreement with previous population studies (25,40,41), Caucasians had substantially higher levels of plasma triglyceride compared with African Americans. Therefore, we hypothesize that the relatively lower triglyceride levels in African Americans may enhance a favorable effect of the apoE genotype, whereas a protective effect of e2 in Caucasians might be offset by higher triglyceride levels.…”
Section: Discussionsupporting
confidence: 79%
“…Fasting plasma CETP activity was approximately 3 times higher (Ϸ250 nmol/mL per h) in CETP and db/CETP mice than is normally found in humans, 5,25 whereas the activity in db mice was negligible. After being fed the atherogenic diet for 16 weeks, the animals were killed and examined for oil red O-positive intimal plaque lesions and intramural fat deposition (Table).…”
Section: Resultsmentioning
confidence: 97%
“…3 Obesity is accompanied by both a mild increase in vascular disease complications 4 as well as elevated plasma CETP activity. [5][6][7][8][9] It is unclear whether this perturbation in CETP activity contributes to altered lipoprotein profiles and elevated vascular disease risk or is a normal consequence of elevated cholesterol levels observed in these patients. 5,10 Interestingly, obese patients with type 2 diabetes have a higher risk of vascular disease complications, 11 higher circulating cholesterol levels, 5,10 and depressed levels of plasma CETP concentrations 5,12 compared with obese nondiabetic controls.…”
mentioning
confidence: 99%
“…Greater fatty acid uptake may be a potential mechanism responsible for the accumulation of intramyocellular lipids. Work from the authors' group has demonstrated that plasma lipids are elevated with obesity (MacLean et al 2000). Thus, intramyocellular lipid accumulation may be a result of greater lipid supply to skeletal muscle and/or up regulated fatty acid transport into the muscle.…”
Section: What Is Causing Intramyocellular Lipid Accumulation?mentioning
confidence: 99%